Excellent performance of electro-assisted catalytic wet air oxidation of refractory organic pollutants. (1st July 2019) - Sun, Min; Zhang, Yu; Kong, Shi-Yu; Zhai, Lin-Feng; Wang, Shaobin
Abstract: Catalytic wet air oxidation (CWAO) is a clean process for the treatment of toxic and/or biorefractory contaminants while it is a challenge to perform the CWAO at room temperature. Herein, we report an electro-assisted CWAO (ECWAO) process using partially oxidized nickel (Ni@NiO) immobilized on a porous graphite felt (GF) as a catalytic anode. Such a process demonstrates extensive effectiveness and good stability in the deep oxidation of various organic pollutants including triclosan (TCS), bisphenol A, ciprofloxacin, sulfamethoxazole, congo red, crystal violent and rodamine B at room temperature. The typical pollutant TCS is rapidly degraded within 105 min with a mineralization efficiency of 86.0 ± 1.4%, at specific energy consumption of 5.3 ± 0.3 kW h kg-TOC −1 . NiO is identified as the catalytically active site at which O2 is dissociated and electro-activated to oxidize the TCS at room temperature. The ECWAO process on the anodic Ni@NiO/GF presents a great potential as an environmental-friendly and energy-saving process for treating high concentrations of refractory organic pollutants under ambient condition. Graphical abstract: Image 102 Highlights: Electrocatalytic air oxidation of organic pollutants is achieved on Ni@NiO/GF. O2 on NiO is activated to chemisorbed oxygen species for organic degradation. The process is rapid and deep oxidation of organics is obtained at low energy cost.